Isolation and Identification of Isocoumarin Derivatives With Specific Inhibitory Activity Against Wnt Pathway and Metabolome Characterization of Lasiodiplodia venezuelensis - Pellissier, Léonie; Koval, Alexey; Marcourt, Laurence; Ferreira Queiroz, Emerson; Lecoultre, Nicole; Leoni, Sara; Quiros-Guerrero, Luis-Manuel; Barthélémy, Morgane; Duivelshof, Bastiaan L.; Guillarme, Davy; Tardy, Sébastien; Eparvier, Véronique; et al. (Frontiers in Chemistry, 2021)
The Wnt signaling pathway controls multiple events during embryonic development of multi-cellular animals and is carcinogenic when aberrantly activated in the adult. Breast cancers are dependent on Wnt pathway overactivation mostly through dysregulation of pathway component protein expression, which necessitates the search of therapeutically relevant compounds targeting them. Highly diverse microorganisms as endophytes represent an under-explored field of therapeutic natural products research. In the present work, the objective was to explore the chemical diversity and presence of selective Wnt inhibitors within a unique collection fungi isolated as foliar endophytes from the long-lived tropical palm Astrocaryum sciophilum. The fungi were cultured, extracted with ethyl acetate, and screened for their effects on the Wnt pathway and cell proliferation. The endophytic strain Lasiodiplodia venezuelensis was prioritized for scaled-up fractionation based on its selective activity. Application of geometric transfer from analytical HPLC conditions to semi-preparative scale and use of dry load sample introduction enabled the isolation of 15 pure compounds in a single step. Among the molecules identified, 5 are original natural products described for the first time, and 6 are new to this species. An active fraction obtained by semi-preparative HPLC was re-purified by UHPLC-PDA using a 1.7 µm phenyl column. 75 injections of 8 µg were necessary to obtain sufficient amounts of each compound for structure elucidation and bioassays. Using this original approach, in addition to the two major compounds, a third minor compound identified as (R)-(-)-5-hydroxymellein (18) was obtained, which was found to be responsible for the significant Wnt inhibition activity recorded. Further studies of this compound and its structural analogs showed that only 18 acts in a highly specific manner, with no acute cytotoxicity. This compound is notably selective for up-stream components of the Wnt pathway and is able to inhibit the proliferation of 3 Triple Negative Breast Cancer cell lines. In addition to the discovery of Wnt inhibitors of interest, this study contributes to better characterize the biosynthetic potential of L. venezuelensis.